2022
DOI: 10.1108/jedt-10-2021-0566
|View full text |Cite
|
Sign up to set email alerts
|

Early supplier involvement framework for reducing construction waste during the design process

Abstract: Purpose The purpose of this paper is to develop a framework to facilitate early supplier involvement (ESI) as an approach for reducing construction waste (CW) generated during the design process. Design/methodology/approach A research methodology consists of literature review, case studies and survey questionnaire was designed to achieve the abovementioned aim. First, the literature review was used to investigate CW, CW generated during the design process, the design process and ESI. Second, two construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…This has improved sustainability (Nielsen and Thomsen, 2011). Othman and El-Saeidy (2022), suppliers provide technical information about materials that reduce waste generation and improve sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has improved sustainability (Nielsen and Thomsen, 2011). Othman and El-Saeidy (2022), suppliers provide technical information about materials that reduce waste generation and improve sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Extant literature on ESI’s impact on work performance is scanty; however, the prospects of its implementation in the manufacturing sector have been overly explored. Generally, ESI implementation is believed to enhance product quality, better manufacturability, shared knowledge and learning and sustainability achievement (Zsidisin and Smith, 2005; Othman and El-Saeidy, 2022; Lahdenpera, 2010). Leenders et al (2006) indicated that a wide range of knowledge could be gained to satisfy the customer’s needs by involving suppliers.…”
Section: Impact Of Early Supplier Involvement On Public Work Procurem...mentioning
confidence: 99%
“…Communication not only leads to more successful outcomes but also breaks down barriers between project team members, improves teamwork abilities, fosters good cooperation and leads to an optimistic project journey for the client. Communication enables project participants to share their knowledge and expertise in order to improve building performance and maintainability (Othman and El-Saeidy 2022). One of the most common reasons that suppliers are not integrated into the design process is a lack of communication among project participants.…”
Section: Enhancing Communication Between Project Participantsmentioning
confidence: 99%
“…ESI helps to improve building design, integrate sustainability elements and reduce waste, as well as to improve building maintenance and meet quality requirements. However, ESI is accompanied with a range of technical, legal, financial, managerial and cultural barriers, which prevent suppliers from participating in the design process (Othman and El-Saeidy, 2022; Saghatforoush, 2014; Chen, 2010). This highlighted the need to overcome these challenges to facilitate ESI in the design process as an approach to enhance building maintainability.…”
Section: Literature Reviewmentioning
confidence: 99%